Facile On‐Site Detection Based on Reactional Wettability Variation. Issue 6 (22nd January 2018) - Lin, Changxu; Xiang, Zheng; Song, Chen; Lin, Youhui; Xu, Mengchun; Wang, Xuefen; Wu, Chenxu; Liu, Xiang‐yang
Abstract: A new on‐site detection strategy is developed based on reactional wettability variation (RWV), which is induced by the coordination reaction between azoimidazole (AzoIm) ligands on an electrospun polymer membrane and the analytes. A sensor unit is fabricated by implanting photoresponsive AzoIm ligands on an electrospun polymer membrane. Contact angle of analyte solution droplets on the membrane surface is varied by coordination reaction between ligands and analytes. The response variation of each analyte is influenced by the membrane‐forming polymer and the conformation of AzoIm. Based on these two factors, the sensor is expanded into a sensor array to offer on‐site detection. The principle component analysis is further applied to evaluate the detection performance and influential structural factors of the array on those ions. The differential response it works on results from varied binding constants of ion–AzoIm complexes and pH of the analyte solutions. Moreover, the detection of metal ions is extended to the bioinorganic molecule of hemin in the same mechanism. It is envisioned that the application of the RWV general pattern can open new possibilities for detection. Abstract : A new sensing strategy based on reactional wettability is introduced. The species and the concentration of metal ions and hemin are reflected on the decrease of the contact angle on the ligand‐containing hydrophobic surface from polymer electrospinning. A sensor array is also exhibited by variating the conformation of photoresponsive ligand and the composition of polymer.